A comprehensive analysis of nanofluids and their practical applications for flat plate solar collectors: Fundamentals, thermophysical properties, stability, and difficulties. (November 2022) - Ajeena, Ahmed M.; Víg, Piroska; Farkas, Istvan
Abstract: The increasing energy demand and continuous confrontation of energy generation costs are preceded by a terrible depletion of fossil fuel power reserves and increased environmental pollution. In the recent years, renewable energy grew quickly to face the responsibility of the unforeseen energy problem. Flat plate solar collectors (FPSC) are well-known and widely used, thus utilised in low and medium thermal different domestic applications. However, FPSCs are less efficient due to their limited ability of solar energy to be converted into thermal energy due to the inefficient heat transfer in solar fluids on the collector's flow tubes. In recent decades, new technologies have enabled the manufacturing of particles in nanometre dimensions (usually less than 100 nm), suspended consistently and stable in traditional solar liquid or so-called nanofluid (NF) and have improved the effects of thermophysical features. The use of NFs as an innovative solar fluid can be reasonably considered as a powerful method of increasing the performance of the FPSC. This paper provides recent advances related to experimental and theoretical studies on NFs applications in the FPSC. Several parameters affecting the thermal efficiency of FPSC are extensively analysed, including the type of nanoparticles (NP)s, size/shape of the NPs, NPs concentration, mass flow rate and solar radiance. This paper also provides a comprehensive review and analysis of progress in the field of NFs, such as the applications of NFs, types, preparation, thermophysical properties, stability, chemical and physical methods for stability, mathematical formulas, and stability evaluation. Finally, the main challenges and future trends mentioned by the researchers while using NFs in solar thermal collectors such as the viscosity, instability, corrosion, operation cost, pumping power, pressure drop and behaviour of surfactant usage, which are assumed helpful to newcomers, are the focus areas of this research.